Abordagens e limitações da Educação Ambiental no Ensino Superior: percepções a partir da disciplina de Gestão Ambiental nos cursos de Graduação em Administração na cidade de Fortaleza - Ce. - Coimbra, Danielle Batista (2011)
The environmental issue has been discussed more significantly over the past 30 years, generating a series of actions to find alternatives to dealing with environmental problems that have become part of everyday society. In this sense, education is now also qualified from the environmental aspect, aiming at the formation of citizens prepared for this new scenario, endowed with consciousness and critical thinking to evaluate and propose solutions for the quality of community life and social justice. Then, Environmental Education emerges as a tool for driving change, with legal recommendations for all levels of formal and informal education. It is believed, howeer, that only an Environmental Education crafted from a critical approach is able to generate the results that society needs. The objective of this work is to evaluate how environmental education have been worked in higher education from the reality of graduate programs in business administration in the city of Fortaleza-Ce, checking the extent to which teaching practices reflect a critical perspective, as well as, how the experiences with the discipline have contributed to students awareness and to adopt different postures in relation to the environment. It is a field, with essentially qualitative approach. The survey was conducted in four institutions of higher education in the city of Fortaleza where teachers and students were interviewed. The results indicate that in these courses, environmental education worked through the discipline of environmental management, also has a conservative bias oriented to market needs and that, despite the discourse of students to be constantly associated with the term "environmental consciousness", the it represents a limited perception of the environment, from an uncritical view.